Existence theorem of finite krasner hyperfields - Yuming Feng; Surdive Atamewoue Tsafack; Ogadoa Amassayoga; Babatunde Oluwaseun Onasanya (Journal of Hyperstructures)
The concern of this paper is to show that there always exist Krasner hyperfields of order n, where n is an integer greaterthan or equal to 2.